La ‘Mitteleuropa’ et l’humain du futur - Adriana Popović (Recherches Germaniques)
As a sculptor of today, I propose a visual form for the human of the future, which I have named ‘multiple body’ or organic cyborg in the sense of Donna Haraway. I build this organorg with influences as varied as my Balkan origins, my readings of science fiction or philosophical, sociological or political essays. My artistic work is built in a kind of resistance to the programmed obsolescence of the body, to its disappearance as foreseen in some SF books and in contemporary art. Corporality is affirmed and everything becomes organic in the organorg. A hybridization, a fusion or even a symbiosis between what the human was, is, will be or would like to be and his environment takes place. My multiple body participates in a war of imaginations by dreaming of possible rebirths and of desirable horizons.